Solar Energy Collector Gain Digital Electronic Meter - Saleim Hachem Farhan; Hassan Ali Salman; Gailan Abdulkader (Journal of Madenat Alelem University College, 2019)
This paper introduces the design and theory of a digital meter for measuring the total useful solar energy gain of a flat – plate collector. This is an important parameter of the collector involved in determining the efficiency. Measurement is carried out in term of the collector fluid inlet temperature Ti, the fluid outlet temperature To, and the mass flow rate m* of the working fluid flowing through the collector. Voltages representative of the variable parameters are assessed and processed using a non-linear analog to digital converter (ADC) and voltage to frequency convertor (VFC) to produce a digital number representative of the solar collector gain.